A comparison of anchor systems for wood shearwalls using the perforated and segmented approaches under various wind loads - Sanchez, Diego (Kansas State University, 2020)
A comparison of anchorage systems for chord elements of wood shearwalls is presented within this report. A rectangular building plan is varied in height and the basic wind speed is varied to achieve an extensive comparison. Buildings of one-, two-, and three-stories are used with three-second gust at 33-feet, Exposure B wind speeds of 115 mph, 140 mph, and 169 mph. Two design approaches, segmented and perforated, are used for the analysis of the shearwalls to determine the number and size of chord elements. The segmented method uses only the full height portions of a shearwall to resist the shear produced by the lateral load; each individual segment is designed to resist the shear and overturning forces induced by the lateral load. While the perforated method uses both the full height segments and segments around openings to resist shear, the wall as a whole is used to resist shear and overturning forces induced by the wind load. The chord elements within the shearwall resist the compression or tension forces produced from the overturning moment. Continuity of the tension elements is achieved by connecting/anchoring the studs, chord elements, from one level to the next. Holdowns are utilized to support the tension produced at the chord elements of the shearwall due to the overturning moment formed in the building from wind pressures. At the base of the wall where the connection to the foundation occurs, anchorage devices, holdowns, are used. Three types of connections are examined to support the tension load in the chord elements for each level: (1) holdown with threaded anchor, (2) embedded holdown, and (3) threaded rod with bearing plate anchorage. Holdown with threaded anchor and embedded holdown are connected at each level of the buildings and threaded rod with bearing plate anchorage spans from bottom to top of the structure. Two holdowns are used in idealized perforated shearwall, while the idealized segmented shearwall uses additional holdowns based on the number of segments. The findings of the parametric study are presented. Holdowns in the perforated approach are larger in size compared to the segmented approach due to the higher tension load produced from overturning. Additionally, the holdowns increase in size with higher wind load on the building.
Keywords: Anchor systems; Segmented approach; Perforated approach; Chord elements; Wood shearwalls